(untitled) (Indian Journal of Animal Production and Management, 2024)
A field survey was conducted in Valsad district of Southern Gujarat to identify various constraints perceived by dairy animal owners in adoption of improved dairy husbandry practices. Information was collected from randomly selected 240 dairy animal owners through personal interview with the help of structured interview schedule. The study revealed that high construction cost (96.25%) and lack of own capital (85.83%) were major constraints in housing practices. Lack of awareness about treatment of poor-quality straw to improve its nutritive value (75.42%), non-availability of green fodder round the year (70.42%) and lack of knowledge of balanced ration (60.83%) were major constraints in feeding practices. Low genetic potential of local animals (89.17%), repeat breeding problems in dairy animals (86.67%) and low conception rate through A.I. (60.42%) were major constraints in breeding practices. Non-remunerative price for milk (90.83%), lack of knowledge in clean milk production (88.75%) and high production cost of milk (83.75%) were major constraints in milking practices. High cost of veterinary medicine (82.50%), lack of awareness of deworming of milch animals (63.75%) and lack of awareness about importance of vaccination (60.83%) were major constraints in adoption of improved health care practices. Hence, better extension services along with development of suitable plan could mitigate the constraints faced by the dairy farmers.